Role of Information and Communication Technology (ICT) in Good Governance Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the growing popularity of Information and Communication Technology (ICT) in different fields, attempts have also been made to implement it in the area of good governance. ICT promotes the idea of digitization of the world in the form of using modern technologies and devices. Good governance as a holistic approach brings the idea of a citizen-friendly, corruption-free and a transparent administrative system. This paper outlines the role played by ICT in the good governance process by advocating the view that in comparison to the developed countries; the developing countries are lagging far behind in getting the benefit of ICT in the good governance process.